1989
DOI: 10.1093/jaoac/72.6.873
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Carbamate Levels in Selected Fermented Foods and Beverages

Abstract: Ethyl carbamate (EC), also known as urethane, is an animal carcinogen and a by-product of fermentation. Because EC has been found in distilled spirits and wines, a variety of fermented foods and beverages were analyzed to assess its occurrence in other products. Previously described methods using a gas chromatograph-thermal energy analyzer with a nitrogen converter were modified for each matrix and gave recoveries of >80%, with a limit of detection in the 1-2 μg/kg(ppb) range. A total of 152 test sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
3
14
0
1
Order By: Relevance
“…In fermented alcoholic beverages the ubiquitous presence of the probable human carcinogen ethyl carbamate (EC) has become a topic of significant concern (Ough 1976a,b;Ingledew et al 1987;Canas et al 1989;Schlatter and Lutz 1990). By itself EC is not carcinogenic; however, products of EC metabolism have been shown to covalently bind DNA thereby inducing mutations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fermented alcoholic beverages the ubiquitous presence of the probable human carcinogen ethyl carbamate (EC) has become a topic of significant concern (Ough 1976a,b;Ingledew et al 1987;Canas et al 1989;Schlatter and Lutz 1990). By itself EC is not carcinogenic; however, products of EC metabolism have been shown to covalently bind DNA thereby inducing mutations.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, winemakers have been actively reducing EC levels in wines by both agricultural practices, wine-making practices and, more recently, molecular biological means (Kitamoto et al 1991;Butzke and Bisson 1998;Yoshiuchi et al 2000;Park et al 2001;Schehl et al 2007). In addition to the presence of EC in table wines, Sake wine, which is a Japanese alcohol made from fermented rice, has some of the highest EC contents amongst fermented beverages; typical Sake wines range from 100 to 250 lg l )1 EC because of a pasteurization process that all Sakes undergo prior to bottling (Canas et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Les agents de cette fermentation peuvent ainsi produire de la citrulline, qui réagit avec l'éthanol pour former du carbamate d'éthyle (ou uréthane). Il a été démontré que ce composé, présent naturellement dans les produits et les boissons fermentés [1,25,26], pouvait, à fortes doses, présenter des effets cancérigènes sur des animaux de laboratoire [23]. Il est donc possible d'envisager à plus ou moins long terme l'instauration d'une législation internationale quant à la teneur en carbamate d'éthyle dans les vins.…”
Section: Introductionunclassified
“…ETHYL CARBAMATE (EC), a well-known carcinogen, has been detected at low concentrations (in the µg/L range) in fermented foods and beverages (Walker et al, 1974;Joe et al, 1976;Canas et al, 1989, Dennis et al, 1989. Lofroth and sGejvall (1971) reported that EC in alcoholic beverages was derived from the reaction between ethanol and diethylpyrocarbonate (DEPC), an antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%